Synthesis of poly(acrylic-co-itaconic acid) through precipitation photopolymerization for glass-ionomer cements: Characterization and properties of the cements. Issue 6 (June 2020) - Abbasi, Raz; Nodehi, Azizollah; Atai, Mohammad
Abstract: Objective: The aim of this study was to synthesize poly(acrylic acid- co -itaconic acid) (PAA- co -PIA) ionomer through a novel precipitation photopolymerization technique. The ionomer was characterized and the effect of its structural parameters, such as molecular weight and copolymer composition were investigated on the mechanical properties of glass-ionomer prepared using the ionomer. Methods: Design of experiment (DOE) was used to examine the effect of monomer ratio and the amount of chain transfer agent on the molecular weight and final conversion of the ionomers synthesized through the precipitation photopolymerization. The copolymer compositions were identified using FTIR and 1 H-NMR spectroscopy. The molecular weights of the copolymers were evaluated by GPC. A series of PAA- co -PIA copolymers were then synthesized via the photopolymerization technique in three monomer ratios and two molecular weight ranges (high and low) to study the properties of the glass ionomers thereof. Experimental dental glass-ionomer cements were prepared by mixing the synthesized polymers with glass powder and their compressive properties were determined according to ISO 9917-1:2007 after storing for 0, 1, 7 and 28 days in distilled water. The scanning electron microscopy (SEM) was used to study the fracture surface morphology of the cements. Results: The PAA- co -PIA polymers were synthesized by the photopolymerization method in a short time and high purity. The DOE showed that by decreasing the acrylic acid/itaconic acid ratio and increasing the amount of transfer agent, the molecular weight and final conversion decreased significantly. By increasing the itaconic acid content in the copolymer composition and increasing the molecular weight in a constant copolymer composition, the compressive strength and modulus were increased. Microstructures revealed that cements made of the higher molecular weight poly acids showed lower cracks and voids. Significance: The precipitation photopolymerization technique provides a promising and facile method in the synthesis of ionomers which are used in dental cements and other application.